Evaluation of the high temperature performance of HfB2 UHTC particulate filled Cf/C composites. Issue 3 (11th February 2017) - Paul, Anish; Rubio, Virtudes; Binner, Jon; Vaidhyanathan, Bala; Heaton, Andrew; Brown, Peter
Abstract: Room and high temperature flexural strength and coefficient of thermal expansion (CTE) of HfB2 ultra‐high temperature ceramic (UHTC) particulate filled Cf /C composites are determined along with UHT oxidation behavior. Both room and high temperature strength of the composites were found to be broadly comparable to those of other thermal protection system materials currently being investigated. The CTE of the composites was measured both along and perpendicular to the fiber direction up to 1700°C and the values were found to depend on fiber orientation by approximately a factor of 3. Arc‐jet testing of the UHTC composites highlighted the excellent ultra‐high temperature oxidation performance of these materials.